Concurrent Solution‐Like Decoloration Rate and High Mechanical Strength from Polymer‐Dispersed Photochromic Organogel. Issue 7 (5th February 2014) - Long, Shijun; Bi, Shuguang; Liao, Yonggui; Xue, Zhigang; Xie, Xiaolin
<x xml:space="preserve">Abstract</x> To achieve a fast photochromic response in solid matrix, photochromic molecules/segments have been either dispersed into elastomers via physical doping or linked to glassy polymers by soft units through covalent bonding. However, the former is lack of high mechanical strength and the latter owes the drawback of time‐consumption of synthesis. Here, we propose a facile strategy of co‐solvent evaporation to prepare polymer‐dispersed photochromic organogel where both high mechanical strength of the glassy polymer matrix and solution‐like fast photochromism of the photochromic molecule within organogel can be retained concurrently. Glassy PVA matrix and dispersed organogel of 1, 3:2, 4‐di‐O‐benzylidene‐d‐sorbitol/poly(propylene glycol) (DBS/PPG) provide high mechanical strength and sufficient free volume for intramolecular rotation of photochromic spiropyran (SP), respectively. Interestingly, these thin films behave a solution‐like decoloration the decay rate of which is 65–70 fold faster than that in the SP‐directly doped PVA film and only slightly slower than those in their corresponding PPG solutions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>